Effective feature selection for real-time stock trading in variable time-frames and multi criteria decision theory based Efficient stock portfolio management - Ullah, A. K. M. Amanat (Brac University, 2021)
This project report is submitted in partial fulfilment of the requirements for the degree of Master of Engineering in Computer Science and Engineering, 2021.